Extracapsular lymph node involvement in ovarian carcinoma - Heublein, Sabine; Schulz, Heiko; Marmé, Frederik; Angele, Martin; Czogalla, Bastian; Burges, Alexander; Mahner, Sven; Mayr, Doris; Jeschke, Udo; Schmoeckel, Elisa (Cancers, 2019)
Ovarian cancer (OC) spread to retro-peritoneal lymph nodes is detected in about one out of two patients at primary diagnosis. Whether the histologic pattern of lymph node involvement i.e., intra-(ICG) or extracapsular (ECG) cancer growth may affect patients’ prognosis remains unknown. The aim of the current study was to analyze the prevalence of ECG and ICG in lymph node positive ovarian cancer. We further investigated whether ECG may be related to patients’ prognosis and whether biomarkers expressed in the primary tumor may predict the pattern of lymph node involvement. Lymph node samples stemming from 143 OC patients were examined for presence of ECG. Capsular extravasation was tested for statistical association with clinico-pathological variables. We further tested 27 biomarkers that had been determined in primary tumor tissue for their potential to predict ECG in metastatic lymph nodes. ECG was detected in 35 (24.5%) of 143 lymph node positive patients. High grade (p = 0.043), histologic subtype (p = 0.006) and high lymph node ratio (LNR) (p < 0.001) were positively correlated with presence of ECG. Both ECG (p = 0.024) and high LNR (p = 0.008) were predictive for shortened overall survival. A four-protein signature determined from the primary tumor tissue was associated with presence of concomitant extracapsular spread in lymph nodes of the respective patient. This work found extracapsular spread of lymph node metastasis to be a common feature of lymph node positive ovarian cancer. Since ECG was positively associated with grade, LNR and shortened overall survival, we hypothesize that the presence of ECG may be interpreted as an indicator of tumor aggressiveness.